Wattpad as Digital Learning Media to Assist Accelerated Third Graders in Writing Narrative Text - Ayunda Ibrahim Haj; Esti Kurniasih (EduInovasi: Journal of Basic Educational Studies, 2024)
Students frequently react negatively when encounter writing lessons and assignments. This happens because writing is one of the most difficult productive skills in English. The lack of innovative and interesting learning media also causes students to be passive and demotivated when learning to write. In the present day, there are many digital writing platforms that can be utilized as learning media to facilitate writing activities. One of them is Wattpad. Therefore, this study aims to explore how Wattpad as digital learning media helps accelerated students in writing narrative texts and describe their narrative writing texts after using Wattpad. Wattpad is one of the biggest online writing platforms that can be used as a learning tool, with a variety of useful features. This study used the qualitative method and was addressed to 31 accelerated students in junior high school. The data collected from observation and documents were analyzed using the Miles and Huberman analysis model. The findings revealed that Wattpad was able to assist accelerated students in writing narrative text by providing them with the platform’s easy access, many reading sources, versatile writing features, and user-interaction features. Furthermore, the accelerated students' narrative writing texts after using Wattpad were diverse in terms of writing levels, reflecting their creativity and narrative writing abilities.